Еуразия даласында тараған екі дөңгелекті арбалар кешені (археологиялық материалдар негізінде) (Journal of history, 2020)
This article is devoted to its main component – the chariot and sources that allow it to conclude that the invention, the existence, structure and history of the Eurasian steppes in the Bronze Age. In our understanding, the chariot – is drawn bridled horses, pole provided with two wheels with spokes carriage open tricycle body used to the war, hunting, sports, ritual ceremonies, as well as a marker of social status of the owner. The image of the horse chariot is one of the most ancient archetypes, firmly rooted in mythology, religion and art of the Indo-European peoples. In the mythology associated with the chariot sled heavenly gods and the sun. Equally important carts and chariots, in particular, have played in the funeral rites of the ancient peoples